O comportamento dos torcedores de futebol e as marcas próprias de uniforme: um estudo de caso da Associação Atlética Ponte Preta - DINIZ, Caio Goncalves de Oliveira (2022)
This academic production is a case study of the original brand of uniforms named 1900, from Associação Atlética Ponte Preta, which aims to identify and understand the behavior of football fans from the perspective of Theories of Practice and the phenomenon of original brands of sports uniforms in Brazil. The investigation starts from the way Campinas fans see the club's initiative to develop its own brand of sports uniforms - a strategy that has been increasingly adopted within Brazilian football, especially by clubs that are not among the biggest in the world. After data collection, which took place through in-depth interviews and document analysis, the data were treated in a qualitative way and organized in order to translate into possible insights that help football club chairmans to treat fans as consumers without ignoring the peculiarities of this group. As a result, it was understood that clubs use their own brands as a way to maximize profits and solve problems inherent in the relationships of medium and small clubs with large suppliers of sports equipment, which in Brazil usually operate in partnership with outsourced companies. Original brands, therefore, emerge to replace brands such as Nike, Adidas and Puma in the club/outsourced company/uniform brand relationship, limiting the agreement only between club and outsourced company, since original brands are managed by the teams themselves.